The Protective Role of Social-Oriented Digital Media Use in Children's and Adolescents' Life Satisfaction During the Covid-19 Pandemic - Laura Marciano; Emiliano Albanese; Kasisomayajula Viswanath; Anne-Linda Camerini (University of Zurich, IKMZ - Department of Communication and Media Research, 2023)
Covid-19 measures have reduced children's and adolescents' life satisfaction (LS), a key indicator of well-being. However, we have limited evidence of the longitudinal associations between changes in LS and different types of digital media use throughout the pandemic. Using data collected in Ticino, Italian-speaking Switzerland from 764 children and adolescents (Mage = 12.51, SDage = 4.00, 52% females) over five months starting from September 2020, the current study investigated temporal variations in LS, and how process-oriented versus social-oriented digital media use predicted LS, controlling for socio-demographic variables. Results of the quadratic latent growth curve model showed a steeper decrease in LS at the beginning of the second wave of the pandemic in Autumn 2020. Process-oriented digital media use predicted lower starting levels (i.e., the intercept) of LS, whereas social-oriented digital media use acted as a protective factor against the initial decrement of LS (i.e., linear slope) and positively influenced the rate of change of LS (i.e., the quadratic slope), pointing towards a faster return to baseline levels. Females, adolescents, participants with low subjective socio-economic status, and non-Swiss participants reported lower levels of LS. Results suggest that when in-person social contacts are compromised, social-oriented use of digital technologies should be promoted in young people to obtain and maintain social contacts that are crucial for LS and their well-being. LS may be conceived as a predisposing condition to accumulate, preserve, and restore mental and social well-being, which, in turn, allow individuals to contribute to their community and society at large.